Operative difficulty grading scale for laparoscopic cholecystectomy at a tertiary care hospital in Eastern Nepal - Sah, Nirmal Prasad; Gupta, Rakesh Kumar; Awale, Laligen; Deo, Kunal Bikram; Sah, Rupesh Prasad; Kumar, Abhijeet; Sah, Suresh Prasad (Journal of Kathmandu Medical College, 2022)
Background: Predictions of difficult cholecystectomy preoperative make the surgeon prepared, thereby making a more careful dissection, back up from senior surgeons, and a low threshold for early conversion. Objectives: To utilise an operative grading scale to predict open conversion, duration of surgery, total length of stay, complications and to validate Nassar score. Methods: This was a prospective cross-sectional study done from 2020 July 9 to 2021 January 30 after ethical clearance among all patients of BPKIHS planned for laparoscopic cholecystectomy for symptomatic gallstone disease. Nassar scale was used for risk evaluation of difficult cholecystectomy. The intraoperative outcome parameters were bleeding, bile spillage, stone spillage, presence of bowel or biliary injury, operative time and conversion to open surgery. Postoperative outcomes noted were total length of stay, 30-day complications, reintervention, and mortality. The data were entered in Microsoft Excel sheet 2010 and analysis was done in SPSS v.26. Results: Seventy-four patients were analysed. Comparison of Nassar scoring system with outcomes revealed a significant association of rising Nassar grade with bile spillage, stone spillage, bleeding, post-surgical drain placement, conversion to open, duration of surgery, and total length of stay. Operative time was significantly more in male, cholecystitis, and interval cholecystectomy. Conversion to open was significantly associated with Nassar grade 4, acute cholecystitis, and interval cholecystectomy. There was no mortality, 30-day reintervention, and complication. Conclusion: Nassar operating scale is simple scale that can be used by all level of surgeons to predict difficult laparoscopic cholecystectomy. Rising grades have significant correlation with difficulty and complications.